Designing a Data-Driven Energy Management Service: A Case Study of South Korea’s National Industrial Complex - Tagir Salakhov; Jaejoon Choi; Minjun Kim (IEEE Access)
Big data plays a crucial role in energy management services by providing valuable insights to customers. However, data analytics alone cannot create value, and it is essential to effectively transform and integrate these data into energy-management services. Although numerous studies have focused on developing data-driven architectures or platforms to manage energy efficiency, few have addressed the design process of data-driven energy management services. To fill this research gap, we conducted a case study to design a novel service concept aimed at improving the energy efficiency of companies within a national industrial complex based on an analysis of electricity consumption data. Finally, our findings, supported by interviews with a small company within the complex, suggest that the proposed information and service concept can be both effective and beneficial for businesses. This study contributes to the integration of data analytics with service design, thereby improving the effectiveness and adoption of such services.